Pelatihan Pengembangan Instrumen Asesmen Berpikir Tingkat Tinggi Bagi MGMP IPA Kabupaten Ogan Ilir - Muhamad Yusup; Abidin Pasaribu; Syuhendri Syuhendri; Anisha Sherany Thamrin; Riska Anggraini (Unram Journal of Community Service, 2022)
Assessment requires not only knowledge but also skills. Meanwhile, not all science teachers in Ogan Ilir understand and receive training on how to assess the desired assessment in the curriculum, especially assessments for higher-order thinking skills. The purpose of this community service activity is for participants to be able to develop higher-level thinking assessment instruments for science learning in junior high schools. The activity was packaged in the form of training which was attended by 22 people from the Ogan Ilir Regency IPA MGMP. Training is carried out with an in-service training (in) - on the job training (on) - in-service training (in) pattern. In the in-service training activity, 1 participant studied and discussed the material presented by the resource person. During on the job training, participants carry out learning activities independently to develop assessment instruments according to the tasks given in in-service training activities 1. In in-service training activity 2, participants reported and discussed the results of activities carried out during on the job training facilitated by the resource persons. The results of the training showed that participants were able to develop assessment instruments. A number of obstacles were encountered in this training. In the process aspect, the main obstacle faced is limited interaction due to the implementation of health protocols due to the Covid-19 pandemic. In the aspect of implementing training results, the main obstacle is the lack of mutual understanding of the importance of training learners to think at a higher level.